2011
DOI: 10.1016/j.ymssp.2010.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Novel adaptation of the demodulation technology for gear damage detection to variable amplitudes of mesh harmonics

Abstract: a b s t r a c tIn this paper, a novel adaptive demodulation technique including a new diagnostic feature is proposed for gear diagnosis in conditions of variable amplitudes of the mesh harmonics. This vibration technique employs the time synchronous average (TSA) of vibration signals. The new adaptive diagnostic feature is defined as the ratio of the sum of the sideband components of the envelope spectrum of a mesh harmonic to the measured power of the mesh harmonic. The proposed adaptation of the technique is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…In addition, a sideband ratio was also calculated using Equation (7); this normalizes the sideband ratio by the gear mesh frequency peak. Prior work by Combet et al [31] has shown this sideband ratio feature to be an effective metric to quantify gear health since it is less susceptible to load fluctuations due to the sideband magnitude being divided by the gear mesh frequency peak [31]. Table 6.2 provides a listing of the frequency domain gear features; a total of 16 were calculated.…”
Section: Frequency Domain Methodsmentioning
confidence: 99%
“…In addition, a sideband ratio was also calculated using Equation (7); this normalizes the sideband ratio by the gear mesh frequency peak. Prior work by Combet et al [31] has shown this sideband ratio feature to be an effective metric to quantify gear health since it is less susceptible to load fluctuations due to the sideband magnitude being divided by the gear mesh frequency peak [31]. Table 6.2 provides a listing of the frequency domain gear features; a total of 16 were calculated.…”
Section: Frequency Domain Methodsmentioning
confidence: 99%
“…Prior work has shown this sideband ratio feature to be an effective metric for quantifying gear health since it is less dependent on the torque load. 18 For each respective gear, four features were calculated, since the sideband ratio and sideband level were calculated for the gear mesh frequency and the first harmonic of the gear mesh frequency. Also, the frequency domain gear features were only calculated for the four gears on the parallel gearbox stage.…”
Section: Frequency Domain Methodsmentioning
confidence: 99%
“…In addition, a sideband ratio was also calculated using ; this normalizes the sideband ratio by the gear mesh frequency peak. Prior work has shown this sideband ratio feature to be an effective metric for quantifying gear health since it is less dependent on the torque load . For each respective gear, four features were calculated, since the sideband ratio and sideband level were calculated for the gear mesh frequency and the first harmonic of the gear mesh frequency.…”
Section: Vibration‐based Signal Processing and Feature Extraction Metmentioning
confidence: 99%
“…Thiringer and Linders focused on the control a wind turbine with fixed pitch angle through controlling rotor speed [4]. Combet and Gelman [5], studied the sideband ratio features to check gear health condition. Generally, in order to investigate the failure root causes and monitor the health condition of WT components, researches count on examined characteristics.…”
Section: Introductionmentioning
confidence: 99%